Substance abuse among the medical students in Central India: an observational study - Marskole, Priyesh; Parmar, Sachin; Yadav, Rashmi; Sethia, Soumitra; Parihar, Leena; Bhagora, Rinku (International Journal Of Community Medicine And Public Health, 2021)
Background: Substance abuse is a pandemic among adults. We carried out this study to know the prevalence of tobacco and alcohol use among II prof MBBS students. The objective was to know the prevalence of tobacco and alcohol use among II prof MBBS students. Methods: An observational study aimed find out the prevalence of alcohol and tobacco abuse. During the period of January 2015 to October 2015 and 100 student from 2nd professional of a medical college from Central India were interviewed using semi structured interview schedules for students. Results: Total students in our study that ever tried alcohol smoking was 62%, among which 47% continued and 53% discontinued. Among 100 participants 55 were male and 45 were female. Out of 100 student 62 were tried alcohol/smoking once in their life time. 13 students were exposed to substance abuse at during their school life, 7 were started during preparation of medical entrance and 42 were started it after coming to college. 12 participants were who were regular using alcohol were belong to family where either one or both parents were doctors among them. Most of the participants were influenced by their friends, 27% were started it for their own gratitude and 9.6% were have seen their family members. 21% participant were involved in indisciplinary activities. Conclusions: The substance abuse is highly prevalent among youngster and the prevalence of substance abuse among female were also significant which is highly alarming situation.